2016
DOI: 10.1074/jbc.m116.729731
|View full text |Cite
|
Sign up to set email alerts
|

Activated G Protein Gαs Samples Multiple Endomembrane Compartments

Abstract: Heterotrimeric G proteins are localized to the plasma membrane where they transduce extracellular signals to intracellular effectors. G proteins also act at intracellular locations, and can translocate between cellular compartments. For example, G␣ s can leave the plasma membrane and move to the cell interior after activation. However, the mechanism of G␣ s translocation and its intracellular destination are not known. Here we use bioluminescence resonance energy transfer (BRET) to show that after activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…However, Gα s , Gγ 2 and AC5 were also not excluded from CCSs and, therefore, it is likely that some of these molecules could be inadvertently internalized together with β 2 AR‐arrestin complexes, and thus participate in signaling in the endosomal compartment. This result is consistent with a previous study that showed the absence of agonist‐stimulated G s accumulation in endosomes, and implies that the stoichiometry of β 2 AR cascade components is likely to differ in plasma membrane and intracellular compartments …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, Gα s , Gγ 2 and AC5 were also not excluded from CCSs and, therefore, it is likely that some of these molecules could be inadvertently internalized together with β 2 AR‐arrestin complexes, and thus participate in signaling in the endosomal compartment. This result is consistent with a previous study that showed the absence of agonist‐stimulated G s accumulation in endosomes, and implies that the stoichiometry of β 2 AR cascade components is likely to differ in plasma membrane and intracellular compartments …”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with a previous study that showed the absence of agonist-stimulated G s accumulation in endosomes, and implies that the stoichiometry of β 2 AR cascade components is likely to differ in plasma membrane and intracellular compartments. 35 Diffusion coefficients observed in our single-molecule experiments for receptors and G proteins in unstimulated cells are generally consistent with previous reports, including Valentine and Haggie 36 and Calebiro et al 37 who also studied β 2 AR. The slightly higher β 2 AR diffusion rates that we observed can be attributed to differences in temperature and possibly cell type (as shown in Valentine and Haggie).…”
Section: Discussionsupporting
confidence: 92%
“…One possible explanation is that [ 3 H]palmitate loading only labels a small fraction of the total G α pool, which cannot be detected using high-performance liquid chromatography. Additionally, another recent study in HEK cells observed redistribution of G α proteins to internal membranes after ISO stimulation, and the authors suggested that such events are independent of the acylation-deacylation cycles ( 59 ). Recent advances in palmitoylation detection methods allow us to better study dynamic palmitoylation of endogenous G α proteins with endogenous lipids and their functional outcomes in specific cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A plasmid encoding the S1 subunit of pertussis toxin was kindly provided by Stephen R. Ikeda (NIAAA, National Institutes of Health, Rockville, MD). Plasmids encoding cerulean–TM–venus, venus–kras, venus–rab5, venus–giantin, and Gβγ–venus have been described previously and were used in this study under conditions that are essentially the same as described previously ( 11 , 22 25 ). Several different GPCR–luciferase constructs were made by appending either Rluc8 or Nluc directly to the receptor C terminus either by QuikChange PCR or by subcloning into pRluc8-N1 or pNluc-N1 vectors.…”
Section: Methodsmentioning
confidence: 99%